Структура Молдовского железорудного месторождения (Украинский щит) по геолого-геофизическим данным и его возможная эндогенная природа - Ентин, В.А.; Гинтов, О.Б.; Мычак, С.В.; Юшин, А.А. (Геофизический журнал, 2015)
На прикладі Молдовського залізорудного родовища (Середнє Побужжя, Україна) викладено уявлення про ендогенну природу залізистих і залізисто-карбонатних порід, що утворюють численні відносно невеликі за розмірами родовища та рудопрояви в Середньому Побужжі, так званому Побузькому залізорудному районі. Це уявлення є альтернативним найпоширеному погляду на осадово-вулканогенно-метаморфогенне походження залізорудних родовищ Українського щита, породи яких зібрані у стиснені складки із субвертикальними крилами із субгоризонтальними шарнірами. An idea of the endogenous nature of ferriferous and ferriferous-carbonate rocks, forming numerous relatively small size of deposits and ore manifestations in the region of the Middle Bug area called Pobuzhsky iron-ore district has been expressed on the example of the Moldovan iron-ore deposit (Middle Bug area, Ukraine). This representation is an alternative for the most commonly held view of the s edimentary-volcanogenic metamorphic origin of iron ore deposits in the Ukrainian Shield the rocks of which are collected in tight folds with subvertical wings and subhorizontal hinges. As a proof of endogenous nature of the Moldovan deposit the results of complex interpretation of magnetic and gravity surveys at a scale of 1:2000-1:5000, the study of physical properties of rocks and deep drilling (1200 m), which indicate the subvertical drop in ore deposits, a completelack of even the initial signs of folding of total collapse and centriclinal or periclinal locking in the structure of deposits have been given in this article. The preliminary isotope analysis of carbonate rock deposits also showed a trend of their composition toward carbonatites.